The determinants of leaf turgor loss point and prediction of drought tolerance of species and biomes: a global meta‐analysis - Megan K. Bartlett; Christine Scoffoni; Lawren Sack (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 393–405 Abstract Increasing drought is one of the most critical challenges facing species and ecosystems worldwide, and improved theory and practices are needed for quantification of species tolerances. Leaf water potential at turgor loss, or wilting (π tlp ), is classically recognised as a major physiological determinant of plant water stress response. However, the cellular basis of π tlp and its importance for predicting ecological drought tolerance have been controversial. A meta‐analysis of 317 species from 72 studies showed that π tlp was strongly correlated with water availability within and across biomes, indicating power for anticipating drought responses. We derived new equations giving both π tlp and relative water content at turgor loss point ( RWC tlp ) as explicit functions of osmotic potential at full turgor (π o ) and bulk modulus of elasticity (ε). Sensitivity analyses and meta‐analyses showed that π o is the major driver of π tlp . In contrast, ε plays no direct role in driving drought tolerance within or across species, but sclerophylly and elastic adjustments act to maintain RWC tlp, preventing cell dehydration, and additionally protect against nutrient, mechanical and herbivory stresses independent of drought tolerance. These findings clarify biogeographic trends and the underlying basis of drought tolerance parameters with applications in comparative assessments of species and ecosystems worldwide.